2020
DOI: 10.3390/ijms21062159
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of PARP-1 Inhibitor 7-Methylguanine

Abstract: 7-Methylguanine (7-MG), a natural compound that inhibits DNA repair enzyme poly(ADP-ribose) polymerase 1 (PARP-1), can be considered as a potential anticancer drug candidate. Here we describe a study of 7-MG inhibition mechanism using molecular dynamics, fluorescence anisotropy and single-particle Förster resonance energy transfer (spFRET) microscopy approaches to elucidate intermolecular interactions between 7-MG, PARP-1 and nucleosomal DNA. It is shown that 7-MG competes with substrate NAD+ and its binding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Previous works on PARP‐1 MD simulations reported the involvement of polar interactions (hydrogen bonding and pi‐cation) and non‐polar interaction (Pi‐stacking) playing crucial roles in the higher activity of ligands in the active site of PARP‐1. Also, previous works described the involvement of van der Waals and hydrophobic interactions in the ligand‐PARP‐1 activities [11,17–19] . Findings from the current study may provide useful insights for the future rational design of novel PARP‐1 inhibitors for the treatment of cancer disease.…”
Section: Introductionmentioning
confidence: 59%
“…Previous works on PARP‐1 MD simulations reported the involvement of polar interactions (hydrogen bonding and pi‐cation) and non‐polar interaction (Pi‐stacking) playing crucial roles in the higher activity of ligands in the active site of PARP‐1. Also, previous works described the involvement of van der Waals and hydrophobic interactions in the ligand‐PARP‐1 activities [11,17–19] . Findings from the current study may provide useful insights for the future rational design of novel PARP‐1 inhibitors for the treatment of cancer disease.…”
Section: Introductionmentioning
confidence: 59%
“…We have chosen 7-methylguanine (7-MG) as a probe PARP inhibitor for the following reasons. (i) 7-MG is a promising competitive inhibitor of the founding family member PARP-1 [ 64 , 65 , 66 , 67 ], (ii) 7-MG is a small NA mimic that occupies only the NA binding region, forming crucial interactions with the Gly863, Ala898, Ser904, and Tyr907 residues [ 51 , 65 ], (iii) high-quality force field parameters of 7-MG are available and ready for use in molecular modeling [ 64 ]. The 7-MG molecule was docked into the NA binding site of PARPs, and then its position was refined using MD simulation and analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…For example, β-amyloid-mediated oxidative stress in Alzheimer’s is accompanied by an increase in the PAR level; PAR also interacts with the α-synuclein that accelerates toxic fibril formation in Parkinson’s disease [ 12 ]. Numerous studies have demonstrated that there is a relationship between PAR and the processes involved in tumorigenesis [ 13 , 14 , 15 , 16 , 17 ]. As early as in 1979, poly(ADP-ribosyl) ation inhibition by nicotinamide analogs was shown to increase the sensitivity of cancer cells to cytotoxic damage [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As early as in 1979, poly(ADP-ribosyl) ation inhibition by nicotinamide analogs was shown to increase the sensitivity of cancer cells to cytotoxic damage [ 18 ]. To date, more than 200 similar compounds are undergoing preclinical and clinical studies as antitumor agents and four poly(ADP-ribose) polymerase (PARP) inhibitors have already been used in practice [ 15 , 19 , 20 , 21 , 22 ]. PAR is involved in cell reprogramming: intense poly(ADP-ribosyl)ation is observed in induced pluripotent stem cells, while inhibition of PAR synthesis reduces the ability of somatic cells transfected with Yamanaka factors (c-Myc, Sox2, and Oct4) to dedifferentiate [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%